2019
DOI: 10.1177/0033354919854448
|View full text |Cite
|
Sign up to set email alerts
|

Parental Incarceration and Child Overweight: Results From a Sample of Disadvantaged Children in the United States

Abstract: Objectives: Rates of childhood obesity and parental incarceration have been increasing in the United States since the 1970s. We examined whether parental incarceration was associated with child overweight at age 9 and whether that association differed by which parent was incarcerated. Methods: We ran cross-sectional logistic regression models predicting the likelihood of a child being overweight, conditional on whether the child’s mother, father, or both parents had ever been incarcerated. Our sample included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
(64 reference statements)
0
10
1
Order By: Relevance
“…Prior family adversity was not significantly associated with BMIz at any wave. Although no prior research has examined the accumulation of family-specific adversity, our results are in contrast with prior studies specific to children of incarcerated parents from Fragile Families ( Branigan and Wildeman, 2017 , 2019 ). These null results have some precedent.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Prior family adversity was not significantly associated with BMIz at any wave. Although no prior research has examined the accumulation of family-specific adversity, our results are in contrast with prior studies specific to children of incarcerated parents from Fragile Families ( Branigan and Wildeman, 2017 , 2019 ). These null results have some precedent.…”
Section: Discussioncontrasting
confidence: 99%
“…Parental imprisonment before child age 5 years was associated with later higher BMI at ages 14, 21, and 30 ( Roettger et al, 2022 ). Decreases in overweight risk have also been observed if one or both parents were ever incarcerated ( Branigan & Wildeman, 2019 ), though two studies have found father incarceration alone was unrelated to risk for childhood overweight ( Branigan and Wildeman, 2017 , 2019 ). Poorer maternal mental health may be linked to higher obesity risk among 10 to 17 year-old, observed in a national study of U.S. children ( n = 14,733) ( Foster et al, 2020 ), though mental health was unrelated to overweight and obesity risk in a study of Australian youth ( Gibson et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven of the 11 studies included in the early childhood to late adolescence section examined self or parent-reported health with mixed findings (Branigan & Wildeman, 2019;Geller et al, 2009Geller et al, , 2012Haskins & McCauley, 2019;Hiolski et al, 2019;Turney, 2014;Turney, 2017). After adjusting for range of covariates (for full list see Table S1), only one study found significant associations between parental incarceration and subjective health.…”
Section: Subjective Healthmentioning
confidence: 99%
“…As recent findings suggest, the timing of parental imprisonment may also constitute an important risk factor for experiencing later adversity ( Branigan & Wildeman, 2019 ; Turney, 2021 ). Our findings suggest that measurement of parental imprisonment in early childhood may be more strongly linked with cardiometabolic health issues for females than might occur in adolescence and adulthood, while other research suggests that physical disability may be of risk to men ( van de Weijer et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among female African Americans in middle-adulthood, Lee and colleagues observed that imprisonment of a family member, including parental imprisonment, was associated with obesity and diabetes ( Lee et al, 2014 ). Two cross-sectional studies have found null associations for paternal imprisonment, and a reduced risk of obesity for maternal or joint parental imprisonment in childhood and early adulthood ( Branigan & Wildeman, 2019 ; Lee et al, 2013 ); these studies are important for helping to establish that the association between parental imprisonment and offspring obesity risk may vary by factors such biological sex, age, and stages in the life course.…”
Section: Introductionmentioning
confidence: 99%